Energizing compassion: using music and community focus to stimulate compassion drive and sense of connectedness - Gilbert, Paul; Basran, Jaskaran Kaur; Plowright, Ptarmigan; Gilbert, Hannah (Frontiers in Psychology, 2023)
Objectives The last 20 years has seen considerable research on the nature and biopsychosocial impacts of compassion training to self and others. This training is usually focused on calming and slowing the mind and body and on individual imagery practices and mantras. This study explored the effects of three variations; 1. The impact of using energising music to generate activation and ‘drive’ for compassion; 2. To focus on imagining ‘breathing in and breathing out a white light or mist of compassion’ to bring compassion to the world ; 3. While listening to energising music, to imagining connecting to the compassion (Sanga) community; imagining oneself as linking with others as part of communities seeking to help the world. Methods From over 4000 members from the Compassionate Mind discussion list participants were invited to take part in a new energising focused self-practise study. The study involved listening to recorded guidance on the evolutionary model of compassion and need to address the potential harmful side of our nature. This was followed by a 4 1/2 minute tonglen-informed guided practice of breathing in and breathing out compassion accompanied by energising music. Forty-three participants completed a number of self-report scales measuring compassion orientation, wellbeing, social safeness and positive affect before and following two weeks of practice. Participant experiences were recorded from a number of open explorative questions. Results Self-report measures taken before and following 2 weeks practice revealed significant increases in: self-compassion, compassion to others, compassion from others, activated positive affect, safe positive affect, social safeness and wellbeing, with the largest effect size relating to compassion for the self (d = -.76). In addition, qualitative data revealed that the participants experienced the practice as energising, inspiring, felt socially connected and that it had significant impacts on other aspects of their lives. Some participants noted that engaging with suffering also stimulated sadness. Conclusions This study found that pairing energising music with breathing practices and specific compassion visualisations, focusing on the desire to bring compassionate to the world and be part of a compassionate community, was well accepted and had a range of significant positive impacts.